Acute Liver Failure Induces Glial Reactivity, Oxidative Stress and Impairs Brain Energy Metabolism in Rats - Guazzelli, Pedro Arend; Cittolin-Santos, Giordano Fabricio; Meira-Martins, Leo Anderson; Grings, Mateus; Nonose, Yasmine; Lazzarotto, Gabriel S.; Nogara, Daniela; da Silva, Jussemara S.; Fontella, Fernanda U.; Wajner, Moacir; Leipnitz, Guilhian; Souza, Diogo O.; et al. (Frontiers in Molecular Neuroscience, 2020)
Acute liver failure (ALF) implies a severe and rapid liver dysfunction that leads to impaired liver metabolism and hepatic encephalopathy (HE). Recent studies have suggested that several brain alterations such as astrocytic dysfunction and energy metabolism impairment may synergistically interact, playing a role in the development of HE. The purpose of the present study is to investigate early alterations in redox status, energy metabolism and astrocytic reactivity of rats submitted to ALF. Adult male Wistar rats were submitted either to subtotal hepatectomy (92% of liver mass) or sham operation to induce ALF. Twenty-four hours after the surgery, animals with ALF presented higher plasmatic levels of ammonia, lactate, ALT and AST and lower levels of glucose than the animals in the sham group. Animals with ALF presented several astrocytic morphological alterations indicating astrocytic reactivity. The ALF group also presented higher mitochondrial oxygen consumption, higher enzymatic activity and higher ATP levels in the brain (frontoparietal cortex). Moreover, ALF induced an increase in glutamate oxidation concomitant with a decrease in glucose and lactate oxidation. The increase in brain energy metabolism caused by astrocytic reactivity resulted in augmented levels of reactive oxygen species (ROS) and Poly [ADP-ribose] polymerase 1 (PARP1) and a decreased activity of the enzymes superoxide dismutase and glutathione peroxidase (GSH-Px). These findings suggest that in the early stages of ALF the brain presents a hypermetabolic state, oxidative stress and astrocytic reactivity, which could be in part sustained by an increase in mitochondrial oxidation of glutamate.